(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The current study was conducted to evaluate the association between the body weight, carcass characteristics and the testis measurements of the three matured cocks of about one year to one and half months of age in the semi arid zone of Nigeria. Sixty matured cocks were used for the study with twenty from each of the genotype. The data collected on the carcass characteristics of the three genotypes of cocks were analyzed using SPSS Version 21 Statistical tool. Differences between treatments means were separated using Duncan’s Multiple Range Test of the same software. The correlations between the different variables were determined using Pearson correlation. The results showed a positive correlation (P< 0.05) between live weight and the internal organs. Also positive significant (P<0.01) relationship were observed between body weight and the slaughter weight (r =0.97). Significant relationship between live weight and the left testis was observed (r =0.67: P<0.01). In conclusion, testis measurement with live weight showed that positive correlation translates into positive genetic correlation among the traits which will lead to improvement in the other traits. This variation may be due to close genetic background of the indigenous cocks